Main Tendencies And Prospects Of Lending To Individuals - Abdunazarov Shokhrux Akrom ugli (Genius Journals, 2024)
In the article, the organizational aspects of lending to individuals and the practical situation of commercial banks in Uzbekistan are studied and researched. The study provides information on the forms, numbers, and dynamics of credit organizations. Also, the organization of the lending process of local commercial banks to individuals, types of loans, and dynamics of loans are analyzed, and some actual issues are identified. Taking this into account, some proposals and recommendations were developed in the future to improve the efficiency of commercial banks in lending to individuals.
Keywords: Uzbekistan; bank; credit